ESG and firm performance: The role of digitalization - Rizky Eriandani; Wahyu Agus Winarno (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This research aims to examine the impact of social, environmental, and governance (ESG) responsibilities on firm performance – books and markets. It also analyzes the role of digitalization in the relationship between ESG and firm performance.Design/Methodology/Approach: The population in this study was all companies listed on the Indonesian Stock Exchange in 2017-2021. The sampling technique used purposive sampling with a total sample of 347 firm-years. Testing hypotheses moderated regression analysis and subgroup analysis.Research findings: Empirical findings demonstrated that ESG responsibilities could improve company performance, both book performance and market performance. On the contrary, digitization could not boost the company's performance. Moreover, digitalization was unable to moderate the relationship between the two. However, when the samples were separated based on digitization variables, the results revealed that ESG had a positive impact on performance only in companies that adopted digital technology.Theoretical contribution/Originality: In addition to enriching literature related to agency and stakeholder theory, this research reinforces empirical evidence of the role of ESG in increasing the value of the company. The results also highlight digital adoption to support environmentally and socially responsible activities. Nevertheless, the impact of digitization on company performance has not been proven. This research contributes to the literature about ESG and digitalization that imply corporate value creation.Practitioner/Policy implication: This research contributes to corporate management to enhance social and environmental responsibility, as well as prompt adoption of digital technology.Research limitation/Implication: This research has some limitations. First, the sample was limited because not all companies in Indonesia had ESG scores in Bloomberg. Second, the measurement of digitalization on the sub-sample only used a dummy and did not differentiate the type of digitization that the company adopted.